Prevalence and Determinants of Needle stick Injury among Nurses: Life Sciences-Medical Science - Arwa Ahmed Al-Mowaraie; Sulafa Al-Qutub; Naif Abdulaziz Al-Harbi (International Journal of Life Science and Pharma Research, 2022)
Needle stick injuries pose a serious risk of transmission of fatal diseases to the workers of the Health care. Globally, more of the reported cases of needle stick injuries happen among nurses than other health professionals. Our aim is to explore the prevalence of needle stick injuries and determinants among nurses for better prevention and control. This is a cross- sectional study where we recruited 282 nurses working at King Fahd Hospital in Jeddah city. The validated self-administered questionnaires were distributed by the head nurse to the participating nurses who were in a direct contact with the patients. From questionnaires we investigated demographics, work-related factors, determinants of needle stick injuries and safety measures. Results of our study showed that about 92% of nurses were females and about 80% regularly take care of 10 patients or less. This study reported a lifetime occurrence of needle stick injury among nurses to be 37.6% (95% CI = 31.9% to 43.3%). The syringe needle was the most common item which caused the recent NSIs among the affected nurses (78.3%), followed by intravenous catheter and tapping needle with prevalence of 11.3% and 7.5% respectively. The occurrence of needle stick injury could not be predicted by nurses’ characteristics such as years of experience, educational level, hours of working and number of patients on duty. However, training on NSIs prevention, Hepatitis B virus vaccination status and availability of safety box in their work place were significant predictors. We conclude that despite the high level of training, awareness, and availability of safety precautions, more than a third of nurses in the KFGH were affected by needle stick injury. Training on NSIs prevention and availability of safety box in their work place were the major determinants of the needle stick injury in KFGH.